SIGNAL MULTIPATH IN HIGH PRECISION GPS SURVEYS - Ata, Ercenk (UNIV OSIJEK, TECH FAC, 2014)
The aim of this paper is to show that GPS signal multipath can significantly influence the accuracy of the results of a GPS survey. For this purpose, Ashtech Z Max GPS receiver, which is the next generation survey solution from Magellan, is used in the obstructed area and investigates the achievable accuracy and repeatability under the same satellite configuration and site condition near a bridge environment. Z tracking and Advanced Multipath Mitigation Technologies (Enhanced Strobe Correlator (ESC)) and Ashtech Max-Trac GPS Antenna) of the Ashtech Z Max ensure the strongest centimetre level position even under weak signal conditions. All of the measurements were performed near a bridge in the two consecutive days. In the analysis, the coordinates of the point, which is located near a bridge, obtained from the same solutions of the ambiguities in the two consecutive days were compared with each other. On the other hand, the results of Ashtech Z Max GPS receiver testing were compared against results from Total Station surveying as a further quality check. The results show that Ashtech Z Max Technology is more stable for the horizontal and vertical coordinates. Positioning accuracy on the centimetre level (1 divided by 2 cm) can be routinely achieved when observing sufficient number of satellites in the multipath environment.
Keywords: GPS (Global Positioning System); multipath; RTK (Real-Time Kinematic); Engineering